UPPER GASTROINTESTINAL TRACT BLEEDINGS (EVALUATION OF 69 PATIENTS) - Vedat GÖRAL,; Yemliha DOĞAN,; Sami KARTI,; Vahit YÜKSELEN,; Halil DEĞERTEKİN,; Fikri CANORUÇ, (Turkish Journal of Gastroenterology, 2020)
-